Presepsi Siswa SMA dalam Peristiwa Banjir - Miftahul Gea Alivia Putri; Ami Widya Pitaloka; Septia Rachma Wulansari; Denisa Tri Wahyuningtyas; I Ketut Mahardika; Singgih Baktiarso (Jurnal Ilmiah Wahana Pendidikan, 2023)
One of the most frequent disasters in Indonesia is flooding which occurs every year. Flooding is a normal natural process that plays an important role in the formation of the earth's plains. There are two parts to the flood process: natural and non-natural processes and the human factor itself. Rain falls to the earth's surface, is retained by plants before entering the soil and flows to lower elevations for evaporation before reaching the ground surface in natural flooding. Floods also occur when there is heavy rainfall. Whereas human activities such as throwing garbage in its place and causing water to flow irregularly, cause non-natural floods where water evaporates, reaches the land, and floods occur. Floods have a negative impact not only on the quantity and quality of ground and surface water, but also on various damaged community environmental facilities.